SPIRIT a highly robust combinational test generation algorithm. - Gizdarski, E. (IEEE Transactions on computer-aided design of integrated circuits and systems)
In this paper, an efficient test pattern generation (TPG) algorithm for combinational circuits based on the Boolean satisfiability method (SAT) is presented. The authors propose a new data structure for the complete implication graph that increases the precision of implication process. Next, they examine approaches like a single-cone processing, single path-oriented propagation, and backward justification and show that they are efficient to improve robustness of TPG algorithms. Finally, the authors propose efficient techniques and heuristics for these approaches. The resultant automatic test pattern generation system, called SPIRIT (Satisfiability Problem Implementation for Redundancy Identification and Test generation), combines the flexibility of the SAT-based TPG algorithms with the efficiency of the structural TPG algorithms. Experimental results demonstrate the robustness of the proposed TPG algorithm. Without fault simulation, SPIRIT is able to achieve 100% fault efficiency for a large set of benchmark circuits in a reasonable amount of time.